Floor plan of John and Phonse Ducey's root cellar, Keels, NL. - Catherwood, Kristin; Millar, Edward; Whitney, Erin (2012)
The root cellar owned by John and Phonse Ducey is located on the eastern outskirts of Keels. It was built in the early 1950s by Henry Thomas Curtis, a carpenter from the nearby community of King’s Cove, for Kenneth Mesh. The cellar consists of an interior structure of poured cement and an exterior layer of wood, with an insulating layer of turf. Phonse Ducey purchased the cellar from Kenneth Mesh in 1990.